The effect of antimicrobial policy implementation on carbapenem resistance: A university hospital experience - Derin, Okan; Şeker, Fatma; Aksoy, Nilay; Yiğit, Pakize; Yılmaz, Mesut; Mert, Ali (Marmara University, 2022)
Objective: The resistance of Gram-negative bacteria to antibiotics is a global issue that leads to increased mortality and treatment costs. The aim of this study is to see how a newly formed carbapenem control team affected the prevalence of carbapenem-resistant Gram-negative rods and antibiotic consumption expenses in 2017 compared to the year before.Methods: The rate of carbapenem antibiotic usage in Intensive Care Units and Bone Marrow Transplantation services, as well as the findings of culture materials obtained from various body parts of the same patients, between January 1, 2016, and December 31, 2017 were assessed.Results: While there was an ordinary restriction on carbapenem consumption in 2016, carbapenem consumption has been more restricted in 2017. The carbapenem-resistant Gram-negative bacteria patterns of culture materials are examined and compared with Defined Daily Dose data of carbapenems. After the restriction, a significant decrease in the consumption of carbapenems was detected. The decline in carbapenem-resistant Gram-negative bacteria and decreasing antibiotic consumption were found to have a moderately positive correlation (r=0.641, p=0.02). A 60.9% decrease was observed in carbapenem costs after carbapenem restriction, on the other hand, an increase in other unrestricted antibiotics was apparent.Conclusion: Antimicrobial restriction policies can help minimize the rate of carbapenem-resistant Gram-negative rods, which is a serious problem in healthcare. We demonstrated that a decrease in carbapenem-resistant Gram-negative rods isolation rates can lead to a decrease in healthcare-associated infections. Although there is no decrease in the direct antibiotics cost, a drop in carbapenem-resistant may lower the expenses of drastic consequences of infections with carbapenem-resistant and its cost. we can conclude that the Antibiotic Control Policy should be modified based on this new information.
Keywords: Carbapenem; Resistance; Gram-Negative Bacteria